Advances in new technologies, interactive interfaces, and communicability First International Conference, ADNTIIC 2010, Huerta Grande, Argentina, October 20-22, 2010, Revised Selected Papers - Cipolla Ficarra, Francisco V.; Castro Lozano, Carlos; Pérez Jiménez, Mauricio; Nicol, Emma.; Kratky, Andreas; Cipolla-Ficarra, Miguel; SpringerLink (Online services). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Advances in New Technologies, Interactive Interfaces, and Communicability, held in Huerta Grande, Argentina, in October 2010. The 16 revised papers presented together with 3 keynote lectures were carefully reviewed and selected from numerous submissions. The topics addressed span the entire spectrum of design, e-commerce, e-learning, e-health, e-tourism, Web 2.0 and Web 3.0. and discuss the latest advances in the areas of accessibility, communicability, computer animation, computer science, database technologies, digital cartography, distance education, GIS, human factors, hypermedia, ICT, quality design, laboratory experience, medical informatics, multimedia, open software, software engineering, telecommunications, telework, tourism online, ubiquitous computing, user-centered design, and virtual reality
Electronic reproduction.
Keywords: Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science